“FORCE MAJEUR CLAUSE” ATAU “HARDSHIP CLAUSE” PROBLEMATIKA DALAM PERANCANGAN KONTRAK BISNIS - Agus Yudha Hernoko (Perspektif, 2006)
The significance of contract is to secure a fair transaction of rights and obligations of the party to the contract, by which it creates a safely properly and beneficially contractual relation. Under no circumstances is the contract made to harm one or both of the parties. Despite fair formation, due to breach of contract or force majeure the contract is not performed as supposed to be. The stipulation of force majeur clause, in some cases, are not accomodative to the business activity because the dispute settlement is usually put in the court. Therefore, there is a new way to apply hardship doctrine which in the perspective of business is seen more flexible and accomodative to solve the dispute. The hardship characteristic, as mention above, is appropriate to the business character which needs both dynamic activity and the business continuity among parties. The implementation of hardship doctrine is a "win-win solution" model which benefits both parties.